Observation of the use of songs in teaching of English pronunciation in the students of sixth year of basic education class “D” at José María Román school, city of Riobamba, Chimborazo province, during the academic term 2016-2017. - Mendoza Ortiz, Diana Isabel (2017)
By means of a previous observation made at the José María Román school with the sixth year students of basic education class "D", it was determined as a problem that the students have difficulties when they pronounce the words in English, even though the teacher applies a good teaching strategy students only practice pronunciation as a repetition without recognizing the different sounds that there is in the English language. This study describes how the English teacher uses the songs to teach pronunciation in English. The research was realized during the academic year 2016 - 2017, with students in the sixth year of basic class "D", the students involved were 33 of whom 15 were men and 18 were women. The purpose of this research is to observe the use of songs in the teaching of English language pronunciation, the type of study is qualitative of exploratory level, the qualitative method used was the ethnographic; the technique used was observation and the instrument was a checklist. The investigation concluded that despite of the methodology used, based on the songs activities, the students continue having problems in pronunciation because the teacher does not perform the activities in a good way.